(untitled) (Bangladesh Journal of Botany, 2022)
Wild edible mushrooms diversity utilized by the community in Gunung Tukung Gede (GTG) nature reserves were observed and documented. The exploration was carried out during September 2018 – June 2019 to collect wild mushrooms and gather information on utilizing wild edible mushrooms by interviewing the indigenous community. About 75 local people who live in Sukatani, Pasilaja, and Cimacan village in GTG nature reserves participated and gave information on utilizing wild mushrooms. The reported edible mushrooms were: Auricularia polytricha, Coprinus sp., Termitomyces albuminosus, T. eurhizus, Boletus edulis, Cantharellus cibarius, Marasmiellus sp., Mycea sp., Pleurotus sp., Volvariella volvacea, Lentinus sajor-caju, Psathyrella sp., Oudemansiella sp., Schizophyllum commune, and Scleroderma sinnamariense. The outcome will contribute information to preserve biodiversity and ecosystems in GTG nature reserves and potential edible mushroom to be used for improving food security. Bangladesh J. Bot. 51(3): 625-629, 2022 (September)